PERANCANGAN APLIKASI SISTEM MONITORING BEBAN TRAFO BERBASIS ANDROID PADA PT. PLN (PERSERO) - Putri Mandarani (Jurnal Teknoif Teknik Informatika Institut Teknologi Padang, 2021)
Abstract Electricity has become an inseparable need of various activities carried out by humans. PT. PLN continues to strive to provide the best service to the community so that the supply of electrical energy can be met. A transformersuyandr can be said to be the heart of transmission and distribution, so a transformer is expected to operate optimally. Transformer load monitoring is an activity to monitor the current status or condition of the transformer. Monitoring the transformer load in the field using hand notes is one of the obstacles that need to be optimized. With a good monitoring system, the availability of electrical energy will always be maintained. The Android-based monitoring system application is designed as a solution to these problems. The application can be operated if the smartphone device used is connected to the internet network. So this application can increase the efficiency of space, time and labor. In this application there are three types of users, namely user, admin and operator. The user is the head of PLN (Persero) who can only see the data from the transformer measurement results. Operators are field officers who use this application to input transformer measurement results. Admin has the authority to input new transformer data and edit and delete measurement data if needed. The Transformer Monitoring System application at PT. PLN (Persero) based on android is designed using android studio, with the Java programming language, and MySQL database.